2014
DOI: 10.3389/fpsyg.2014.00081
|View full text |Cite
|
Sign up to set email alerts
|

Model fit evaluation in multilevel structural equation models

Abstract: Assessing goodness of model fit is one of the key questions in structural equation modeling (SEM). Goodness of fit is the extent to which the hypothesized model reproduces the multivariate structure underlying the set of variables. During the earlier development of multilevel structural equation models, the “standard” approach was to evaluate the goodness of fit for the entire model across all levels simultaneously. The model fit statistics produced by the standard approach have a potential problem in detectin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
106
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(114 citation statements)
references
References 23 publications
(36 reference statements)
2
106
1
Order By: Relevance
“…However, the overall fit measures could potentially fail to identify misfit on the between level because the much larger sample size of the within level dominates the overall fit. To thoroughly assess the model fit, we apply the partial saturated method developed by Ryu and West (; see also Ryu ) and manually calculate level‐specific fit indices. This procedure yields acceptable fit on the within (CFI = 0.92, RMSEA = 0.03) and between level (CFI = 0.97) (more information on this method can be found in Online Appendix ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the overall fit measures could potentially fail to identify misfit on the between level because the much larger sample size of the within level dominates the overall fit. To thoroughly assess the model fit, we apply the partial saturated method developed by Ryu and West (; see also Ryu ) and manually calculate level‐specific fit indices. This procedure yields acceptable fit on the within (CFI = 0.92, RMSEA = 0.03) and between level (CFI = 0.97) (more information on this method can be found in Online Appendix ).…”
Section: Discussionmentioning
confidence: 99%
“…As instructional quality and the motivational constructs were measured at both the student and the classroom level, we tested for measurement invariance at these two levels by conducting (a) single-level MGCFA, and (b) multilevel MGCFA. For the latter, the student (individual) level was saturated, assuming only correlations among all items of a scale (Ryu 2014). For the school climate constructs, however, only (b) applied, because they were measured by teacher ratings.…”
Section: Discussionmentioning
confidence: 99%
“…According to Balakrishnan et al (2016) and Meyers et al (2006), there are more than 20 fit indices and no agreement which to report for measuring the hypothesized model. According to Balakrishnan et al (2016), Ryu (2014), and Byrne (2009), these measures have been characterized into four indices categories such as: 1) absolute fit index, 2) Relative fit index, 3) Noncentrality based index and 4) Parsimonious fit index. Complete cut off results for the considered indices of this study have been reported in Table 5.…”
Section: Fit Measuresmentioning
confidence: 99%